Habitual sleep duration of coaches during in-competition and out-of-competition - Ong, Lydia Jingya (2019)
Background: Many coaches lack enough sleep due to their hectic schedules and stress over competitions. Insufficient sleep may result in coaches feeling tired most of the time and this may impact their coaching behaviors and performance. There are much focus and interest in the sleep and performance of athletes. However, minimal studies have been done on coaches. Coaches are known to have a strong and direct impact on their athletes. Therefore, sleep is important to athletes as well as their coaches. Purpose: This research aims to examine if there is a difference between coaches’ sleep duration during in-competition (Institute-Varsity-Polytechnic Games) and out-of-competition period. Another aim is to investigate if coaches’ sleep duration is correlated with coaching behavior. Method: 7 participants (4 male, 3 female, age 37 ± 10.5) from various sports; years of coaching experience 14 ± 8.5 and their respective 50% of athletes in the team, total of 28 athletes (16 male, 12 female, age 21 ± 2.4) completed questionnaires during two observed training sessions. Results: Paired-samples t-test of coaches’ sleep duration and competition period revealed significant differences. In-competition (M=364.29, SD=50.28) and out of competition (M=450, SD=38.73) conditions; t(6)=8.40, p=0.016. Pearson correlation of combined sleep duration and coaching behavior revealed significant correlations. Conclusion: Coaches have longer and better sleep quality during out-of-competition period. Coaches showed more positive behaviors and less negative behaviors during the out-of-competition training session compared to in-competition training.